The promised Neverland. 16 - Shirai, Kaiu (VIZ Media, LLC, 2020)
While attempting to locate the Seven Walls, Emma and Ray find themselves trapped in a mysterious world. Can they escape this labyrinth and make the promise that will finally bring about peace? Meanwhile, Norman has his own plans<U+2026>